Uncertainty communication in the environmental life cycle assessment of carbon nanotubes. (2015) - Parsons, S.; Murphy, R.J.; Lee, J.; Sims, G.
Amidst the great technological progress being made in the field of nanotechnology, we are confronted by both conventional and novel environmental challenges and opportunities. Several gaps exist in the present state of knowledge or experience with nanomaterials. Understanding and managing the uncertainties that these gaps cause in LCAs is essential. Traditionally used for more established technology systems, environmental LCA is now being applied to nanomaterials by policymakers, researchers and industry. However, the aleatory (variability) and epistemic (system process) uncertainties in LCAs of nanomaterials need to be handled correctly and communicated in the analysis. Otherwise, the results risk being misinterpreted, misguiding decisionmaking processes and could lead to significant detrimental effects for industry, research and policymaking. Here, we review current life cycle assessment literature for carbon nanotubes, and identify the key sources of uncertainty that need to be taken into consideration. These include: the potential for nonequivalency between mass and toxicity (potentially requiring inventory and impact models to be adjusted); the use of proxy data to bridge gaps in inventory data; and the often very wide ranges in material performance, process energy and product lifetimes quoted.